Public administration and legal regulation effectiveness in the field of health care in the context of sustainable development - Hutsaliuk, O.; Storozhuk, O.; Zhovnirchyk, Ya.; Zaiarniuk, O.; Kartsyhin, D.; Сторожук, О. В.; Заярнюк, О. В. (My University, 2020)
The purpose of the article is the study of health capital as the basis for the formation of human capital. The authors consider health capital as a new factor in economic growth in modern conditions. It is concluded that there is a high risk of a shortage of health capital due to high mortality, low fertility, and low life expectancy. There is also a shortage of investment in health care. The regional features of the development of the health capital of Ukraine in modern conditions are analyzed. The existence of regional differences in the formation of health capital is proved. The inconsistency of regional and national interests regarding the strategy of state regional policy is revealed. It is concluded that regional priorities should be such as to save and increase the health capital of health. The results of an integrated assessment made it possible to form a ranking of regions by indicators proposed by the authors to ranking the regions make it possible to develop programs of priority measures to implement the strategic goal of healthcare. It is an increase in the quality and accessibility of medical care, drug provision, ensuring the sanitary and epidemiological safety of the country, and the prevention of infectious diseases among the population of health capital. The approaches proposed by the authors to ranking the regions make it possible to develop programs of priority measures to implement the strategic goal of healthcare. It is an increase in the quality and accessibility of medical care, drug provision, ensuring the sanitary and epidemiological safety of the country, and the prevention of infectious diseases among the population.
Ефективність державного управління та правового регулювання в галузі охорони здоров'я в умовах сталого розвитку
Keywords: human capital; health capital; regional development; health capital index; державне управління; правове регулювання; охорона здоров'я